ANALYSIS OF AL-MUQOBALAH IN SURAH AR-RAHMAN IN STUDYING THE BEAUTY OF LANGUAGE - Bebi Khairani; Dita Andini Harahap; Rahma Aswani; Harun Al-Rasyid (Yayasan Haiah Nusratul Islam, Indonesia, 2024)
This research aims to analyze the use of al-muqabalah (contradictions of meaning) in Surah Ar-Rahman. Al-muqabalah is a form of the beauty of the language of the Koran which is included in the study of the science of balaghah. The method used is a qualitative approach to the type of library research. The research's primary data is the verses of Surah Ar-Rahman which contain muqabalah elements, while the secondary data comes from balaghah books and related literature. Data collection techniques use documentation and literature study methods. The findings of the research indicate that Surah Ar-Rahman contains various forms of muqabalah, such as the muqabalah between verses of nature, the muqabalah contrasting worldly and afterlife blessings, as well as the muqabalah between paradise and hell. The application of muqabalah in this surah aims to enhance the meaning, clarify the purpose of the verses, and highlight significant messages within the surah. This study is anticipated to offer a deeper insight into the rhetorical style of the Qur'an, especially regarding the use of muqabalah in Surah Ar-Rahman. translit ke bahasa indonesia